PERBEDAAN MOTIVASI KERJA ANTARA KARYAWAN KONTRAK DAN KARYAWAN TETAP PADA PT. BANK RAKYAT INDONESIA CABANG CIMAHI - Arif, Fajar Purnama (Psympathic : Jurnal Ilmiah Psikologi, 2018)
This research used comparative study to compare motivation between contracted employee and permanent employee who work at PT Bank Rakyat Indonesia Cimahi branch. Sample are 40Â employee represent teller and customer service division. Qualitative study is used with comparative analysis. Instrument used is Motivation Assesment Inventory from Denies C Kinlaw (1981. Data analysis result probalility more than 0,5 so that HoÂ is accepted and H1Â is rejected. It is concluded that there is different work motivation between contracted employee and permanent employee.